2020
DOI: 10.3390/app10248968
|View full text |Cite
|
Sign up to set email alerts
|

Heat Loss Coefficient Estimation Applied to Existing Buildings through Machine Learning Models

Abstract: The Heat Loss Coefficient (HLC) characterizes the envelope efficiency of a building under in-use conditions, and it represents one of the main causes of the performance gap between the building design and its real operation. Accurate estimations of the HLC contribute to optimizing the energy consumption of a building. In this context, the application of black-box models in building energy analysis has been consolidated in recent years. The aim of this paper is to estimate the HLC of an existing building throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…In several studies, vector-based analyses has been used to resolve many problems related to the technical sciences. For example, one can find methods based on vector analysis in acoustics [20], building planning [21], and other technical topics [22]. However, during research using a large international database, we did not find any usage of vector analysis in the industrial management field.…”
Section: Introductionmentioning
confidence: 79%
“…In several studies, vector-based analyses has been used to resolve many problems related to the technical sciences. For example, one can find methods based on vector analysis in acoustics [20], building planning [21], and other technical topics [22]. However, during research using a large international database, we did not find any usage of vector analysis in the industrial management field.…”
Section: Introductionmentioning
confidence: 79%
“…These datasets are necessary to obtain an efficient hyperplane that defines the boundary line for effective learning. MLP and SVR models are considered black box models with difficulty understanding internal mechanisms (Martínez-Comesaña et al, 2020;Stollfuss and Bacher, 2022), although research into model explainability is gaining attention (Molnar et al, 2020). The reduced performance observed in MLP and SVR models could be related to the complexity of their model parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Tools and methods are needed that take into account the time, probability of events, threats, and the need for functional flexibility of buildings. This involves access to integrated information, interdisciplinary observation of phenomena and the structuring of large amounts of data (on the basis of D'Amico; A., Bergonzoni; G., Pini; A.; Currà, E, 2020; Marques, G.;Pitarma, R. A, 2019;Martínez-Comesaña, M. et al, 2020). Among the recent studies observed is, for example, the analysis of current limitations in residential buildings in relation to the phenomenon of the current epidemic.…”
Section: Introduction Health Aspects In Architectural Design On the Background Of Sustainability Goals Methodology Of Research In Case Stmentioning
confidence: 99%